A formação de professores de língua inglesa a partir da ótica freireana: autoritarismo, autoridade e autonomia - Simoneli, Barbara Cortat (2023)
The main objective of this research was to carry out analyzes and reflections on the training of English teachers today from the Freirean perspective, focusing on the concepts of authoritarianism, authority and autonomy. It was relevant to analyze the training of English teachers today to seek ways for teachers to leave undergraduate courses prepared to deal with the classroom context and its problems in a critical way and become able to provide teachinglearning processes meaningful for their students. The theoretical framework used includes Paulo Freire's perspectives and his development of the concepts of authoritarianism, authority and autonomy in the area of education, among other related ones. In addition to Freire himself, I brought commentators of this scholar who also discuss and add to his theorizations and conceptualizations. The literature review included studies on teacher training, especially English language teachers, at their different levels, undergraduate (Supervised Internship – Estágio Supervisionado) and graduate (Teaching Internship - Estágio Docência), and studies on the COIL (Collaborative Online International Learning) and its relationship with the training of English teachers. The methodology employed is autoethnography (Pardo, 2019; Fadini, 2020), crossed by bonds and affections, in which I analyzed field diaries that I produced throughout the formative experiences that I lived and attended to. Data analysis indicates that the training of English teachers, especially the disciplines of Supervised Internship I and II (Estágio Supervisionado I e I) and Teaching Internship (Estágio Docência), have a strong potential for the development of teaching authority and the autonomy of students and educators if the relationships, dynamics and teaching methods employed are geared towards this, especially if they are dialogical, problematizing, reflective, liberating and active, going against the grain of authoritarian relationships, dynamics and teaching methods. Furthermore, it was shown that the process of developing autonomy and authority is not linear, but is complex and continuous, as we are inconclusive beings.